Where is the Detection Limit? - Eliasson, Mattias; Furufors, Anders; Glasell Johansson, Linnea; Lundqvist, Thomas; Roderus, Jens (My University, 2016)
This report investigates the detection efficiency of the experimental setup LAND/R3B. This is done through Monte Carlo simulations. The simulation software geant4, via the wrapper program ggland, is used with the reconstruction tool land/r3b-tracker. Beams of different isotopes of carbon, boron and beryllium, produced by reactions of parent isotopes 16C, 17C and 18C, were simulated passing through the setup. The land/r3b-tracker reconstructs the nuclear masses and momentum 4-vectors of the ions from the data acquired by the detectors. The efficiency is determined assuming the nuclear masses follow a normal distribution. Events that fell inside the distribution were considered correctly reconstructed. The detection efficiency is the quotient of the correctly reconstructed events and the total number of simulated events. It was found that this efficiency depends on several variables, where the geometry of the detectors is one. The detector GFI2 (Groer FIberdetektor 2) was found to be the detector that has the lowest acceptance. The addition of transverse momentum to the ions was also found to affect the efficiency.
Keywords: Biologiska vetenskaper; Grundläggande vetenskaper; Hållbar utveckling; Annan teknik; Energi; Innovation och entreprenörskap (nyttiggörande); Biological Sciences; Basic Sciences; Sustainable Development; Other Engineering and Technologies; Energy; Innovation & Entrepreneurship